Kilometer-precise (UII) Umbriel physical properties from the multichord stellar occultation on 2020 September 21 - Assafin, M.; Santos-Filho, S.; Morgado, B. E.; Gomes-Júnior, A. R.; Sicardy, B.; Margoti, G.; Benedetti-Rossi, G. [UNESP]; Braga-Ribas, F.; Laidler, T.; Camargo, J. I.B.; Vieira-Martins, R.; Swift, T.; et al. (Oxford University Press (OUP), 2023)
We report the results of the stellar occultation by (UII) Umbriel on 2020 September 21. The shadow crossed the USA and Canada, and 19 positive chords were obtained. A limb parameter accounted for putative topographic features in the limb fittings. Ellipse fittings were not robust – only upper limits were derived for the true size/shape of a putative Umbriel ellipsoid. The adopted spherical solution gives radius = 582.4 ± 0.8 km, smaller/close to 584.7 ± 2.8 km from Voyager II. The apparent ellipse fit results in a true semi-major axis of 584.9 ± 3.8 km, semi-minor axis of 582.3 ± 0.6 km, and true oblateness of 0.004 ± 0.008 for a putative ellipsoid. The geometric albedo was pV = 0.26 ± 0.01. The density was ρ = 1.54 ± 0.04 g cm−3. The surface gravity was 0.251 ± 0.006 m s−2 and the escape velocity was 0.541 ± 0.006 km s−1. Upper limits of 13 and 72 nbar (at 1σ and 3σ levels, respectively) were obtained for the surface pressure of a putative isothermal CO2 atmosphere at T = 70 K. A milliarcsecond precision position was derived: α = 02h30m28s.84556 ± 0.1 mas, δ = 14o19́36́́.5836 ± 0.2 mas. A large limb parameter of 4.2 km was obtained, in striking agreement with opposite Southern hemisphere measurements by Voyager II in 1986. Occultation and Voyager results indicate that the same strong topography variation in the surface of Umbriel is present on both hemispheres.
Keywords: occultations; planets; satellites: individual: (UII) Umbriel